Enhanced cognition and emotional recognition, and reduced obsessive compulsive symptoms in two adults with high-functioning autism as a result of deep Transcranial Magnetic Stimulation (dTMS): a case report. Issue 3 (4th July 2017) - Avirame, Keren; Stehberg, Jimmy; Todder, Doron
ABSTRACT: We report reduced repetitive behaviors similar to obsessive compulsive disorder and improved emotional recognition and cognitive abilities in two young patients diagnosed with high-functioning Autism as a result of deep transcranial magnetic stimulation (dTMS). The patients received daily high-frequency (5 Hz) dTMS with HAUT-coil over the medial prefrontal cortex for a period of 5–6 weeks. A computerized cognitive battery, tasks for testing emotional recognition, and clinical questionnaires were used to measure the effects of treatment. TMS might have modulated networks related to metalizing abilities and self-referential processes since both patients reported improved sociability and communication skills.